Don't Mix Business with Politics? - Understanding Stakeholder Reactions to Corporate Political Activism - Moritz Appels; Laura Marie Edinger-Schons; Daniel Korschum; Luisa Balk (Marketing Review St.Gallen, 2020)
A growing number of corporations and CEOs take stands on socio-political issues such as gun ownership or immigration. Based on an empirical study including 488 respondents assessing 60 real cases of corporate political activism of the last years, this paper explains how practitioners can maximize positive stakeholder reactions in doing so.
Keywords: 650